2022
DOI: 10.1007/s00268-022-06446-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Non‐Operative Management of Uncomplicated Acute Appendicitis Compared to Appendectomy: An Umbrella Review of Systematic Reviews and Meta‐Analyses

Abstract: Background Non-operative management (NOM) of uncomplicated acute appendicitis (AA) has been introduced as an alternative to appendectomy. This umbrella review aimed to provide an overview of the efficacy and safety of NOM of uncomplicated AA in the published systematic reviews. Methods This umbrella review has been reported in line with the PRISMA guidelines and umbrella review approach. Systematic reviews with and without meta-analyses on the efficacy of NOM of AA were analyzed. The quality of the reviews was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 46 publications
2
14
0
1
Order By: Relevance
“…Indeed, several recent prospective randomized control trials both in Europe and the USA have demonstrated non-inferiority of antimicrobial-based pharmacologic management of early-stage acute appendicitis compared with appendectomy [15][16][17][18][19]. While these results have been met with great interest, and have provided therapeutic alternatives in the appropriate patient, the incidence of recurrent acute appendicitis, principally in patients with an appendicolith, ranging from 24 to 31%, is seen by some as a failure of non-operative management [20,21]. Thus, outcomes related to surgical removal of the appendix remain of great importance for surgeons, Emergency Medicine clinicians, Primary Care physicians, as well as patients and their families.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several recent prospective randomized control trials both in Europe and the USA have demonstrated non-inferiority of antimicrobial-based pharmacologic management of early-stage acute appendicitis compared with appendectomy [15][16][17][18][19]. While these results have been met with great interest, and have provided therapeutic alternatives in the appropriate patient, the incidence of recurrent acute appendicitis, principally in patients with an appendicolith, ranging from 24 to 31%, is seen by some as a failure of non-operative management [20,21]. Thus, outcomes related to surgical removal of the appendix remain of great importance for surgeons, Emergency Medicine clinicians, Primary Care physicians, as well as patients and their families.…”
Section: Discussionmentioning
confidence: 99%
“…Por otra parte, el presente estudio mostró como en los pacientes tratados con apendicectomía se reportó una menor estancia hospitalaria y un mayor éxito terapéutico. Sobre este tema, Emile et al 25 realizaron una revisión "umbrela" en el año 2022, que incluyo 18 revisiones sistemáticas, concluyendo que la evidencia existente muestra como el manejo no quirúrgico se asoció con un mayor fracaso terapéutico y una estancia más corta comparada con la apendicectomía, estos resultados muestran como el manejo con terapia antibiótica requiere una selección y observación cuidadosa de los pacientes.…”
Section: Discussionunclassified
“…Decisionmaking regarding elective IA is often left to the discretion of children's caregivers' preferences in North America, as both management approaches have similar rates of low complications. 12 Parents facing the decision of whether or not to have their child undergo elective IA may face decisional conflict. For example, at our institution there are many instances where parents express decisional conflict regarding this elective procedure.…”
Section: Background and Rationalementioning
confidence: 99%
“…In cases where there are multiple viable treatments, decision-making can be difficult, especially among pediatric patients. Decision-making regarding elective IA is often left to the discretion of children’s caregivers’ preferences in North America, as both management approaches have similar rates of low complications 12…”
Section: Background and Rationalementioning
confidence: 99%
See 1 more Smart Citation